New Approaches in Foundation Engineering - Yilmaz, Salih, editor 650203 (London : IntechOpen, 2022)
Many catastrophic building failures are due to inadequate knowledge of soil behavior. As such, foundation engineering is an important part of structural design. This book provides a comprehensive overview of foundation engineering. Chapters address such topics as the properties of tropical soils in Brazil, glass fiber-reinforced soils, carbon-reduced foundations of high-rise structures, intelligent design of underground powerhouses, and karst protection design.